Potential impact of climate change in sugarcane and mitigation strategies in Zimbabwe - Chandiposha, Misheck (Academic Journals, 2016)
Sugarcane production is important to the economy of Zimbabwe by contributing to Gross Domestic Product (GDP), employment creation and foreign currency generation. However, its production is likely to be affected by climate change due to projected increase in temperature and changing rainfall patterns. This paper reviews the possible effects of climate change in the agronomy of sugarcane. Temperature rise due to climate change is projected to increase cane growth during winter although it may result in increased irrigation needs. Increased temperature will also alter the prevalence of weeds diseases and insect pests in sugarcane production. The changing rainfall patterns due to climate change may result in water stress induced by drought although harversting efficiency is expected to increase. The paper also expounds on the mitigation and adaptation strategies that can be employed in the sugarcane industry as a way of reducing losses in sugarcane production.